PENGARUH SOSIALISASI KEBIJAKAN LINGKUNGAN TERHADAP KESADARAN MASYARAKAT DALAM MEWUJUDKAN KEBERSIHAN LINGKUNGAN DI KAMPUNG MAJLIS PANYAIRAN KELURAHAN PALABUHANRATU - Dewi Fitriani; Atot Sugiri (STISIP Widyapuri Mandiri, 2022)
This study uses a quantitative approach. The population of this study was the entire family head of Majlis Panyairan Village, Palabuhanratu Village, amounting to 339 people, with a total sample of 102 people and carried out using proportionate simple random sampling technique and taken 30% of the total population. The calculation results show that the average item variable for policy socialization on environmental hygiene in Majlis Panyairan Village, Palabuhanratu Village, Sukabumi Regency is 3.48 or 69.60% of the ideal value and is included in the good category, while the average score of the community awareness variable in Majlis Village Panyairan Palabuhanratu Village in realizing environmental cleanliness is 3.36 or 67.20% of the ideal value and is included in the sufficient category. The results of statistical analysis obtained that the price of rXY = 0.534 is included in the fairly strong category. With a significance value (2-tailed) 0.000 <0.05 or tcount = 6.311 > ttable = 1.984, so it can be concluded that the socialization of policies on environmental cleanliness (X) on public awareness in realizing environmental cleanliness (Y) in Majlis Panyairan Village, Palabuhanratu Village . The coefficient of determination (KD) of 28.52% the value of the community awareness variable in realizing environmental cleanliness (Y) in Majlis Panyairan Village, Palabuhanratu Village can be explained by the variable of policy socialization on environmental cleanliness (X), and the remaining 71.48% is determined by other factors . While the linear regression equation model obtained is Y = 19.650 + 0.525X. Therefore, to increase public awareness in realizing environmental cleanliness, it is recommended that the Palabuhanratu Sub-district Government, Sukabumi Regency, be more active in disseminating policies on environmental hygiene.